2019
DOI: 10.1111/1753-6405.12926
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of recently arrived Asian men who have sex with men diagnosed with HIV through sexual health services in Melbourne and Sydney

Abstract: Objectives: Asian men who have sex with men (MSM) who have recently arrived in Australia are an emergent risk group for HIV; however, little is known about how they compare to Australian MSM diagnosed with HIV. This study compared the characteristics of these two groups. Methods: A retrospective, cross‐sectional study of MSM diagnosed with HIV between January 2014 and October 2017 in Melbourne and Sydney public sexual health clinics. Asian MSM were those who had arrived in Australia within 4 years of diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…Our findings show that Medicare‐ineligible MSM are less likely to report condomless sex with male partners, despite anorectal chlamydia being more common among Medicare‐ineligible MSM compared to Medicare‐eligible MSM. Our finding is consistent with a previous Australian study showing anorectal chlamydia was more commonly detected in Asian‐born MSM (who are predominately Medicare‐ineligible) compared to Australian MSM (who are Medicare‐eligible) newly diagnosed with HIV 9 . The reasons of this difference are unclear, but it is possible that the actual sexual risk might be under‐reported due to language barriers or cultural factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings show that Medicare‐ineligible MSM are less likely to report condomless sex with male partners, despite anorectal chlamydia being more common among Medicare‐ineligible MSM compared to Medicare‐eligible MSM. Our finding is consistent with a previous Australian study showing anorectal chlamydia was more commonly detected in Asian‐born MSM (who are predominately Medicare‐ineligible) compared to Australian MSM (who are Medicare‐eligible) newly diagnosed with HIV 9 . The reasons of this difference are unclear, but it is possible that the actual sexual risk might be under‐reported due to language barriers or cultural factors.…”
Section: Discussionsupporting
confidence: 90%
“…The reasons of this difference are unclear, but it is possible that the actual sexual risk might be under‐reported due to language barriers or cultural factors. Furthermore, previous research has shown that Medicare‐ineligible MSM, including international students, have a higher prevalence of STIs in comparison with Medicare‐eligible MSM 9 . Most of these Medicare‐ineligible individuals originated from south‐east and central Asia, where the stigma surrounding homosexuality is highly prevalent and sexual health literacy levels are quite low 15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIV epidemic has changed during the 2010s [33]. Before the COVID-19 pandemic, new HIV diagnoses among Australian-born MSM were decreasing but new HIV diagnoses among overseas-born MSM were increasing, particularly individuals who are recently arrived migrants and international students [33][34][35][36]. Given Australia has closed its border to international travellers, fewer migrants and international students would have been tested for HIV in 2020 than in 2019 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual identity concealment, in turn, is associated with worse mental health outcomes [15], a decreased sense of belonging, and social isolation [4,16]. In Australia, Asian-born gbMSM are more likely to have advanced HIV upon diagnosis but to report fewer numbers of male sexual partners compared to Australian-born gbMSM [17]. This may indicate an underlying stigma related to HIV and sexual identity, particularly given the reported prevalence of such stigma in several Asian countries [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%